Greek Bronze Statuary : From the Beginnings Through the Fifth Century B.C. - Mattusch, Carol C. (Cornell University Press, 2019)
Freestanding bronze statuary was the primary mode of artistic expression in classical Greece, yet it was not until the nineteenth century that any original large statues of that period were unearthed. Although ancient literature has preserved information about the most famous Greek sculptors who worked in bronze, our perception of the art has been limited by the small number of extant originals from the sixth and fifth centuries B.C. there remain fewer than ten large cast bronze statues, a like number of bronze heads, an assortment of fragments, and some clay molds for casting. Carol Mattusch enriches our knowledge of this beloved but elusive art form in a comprehensive study of the style and techniques of bronze statuary during the Archaic (6th century B.C.) and Classical (5th century B.C.) periods.